Emerging chalcogenide thin films for solar energy harvesting devices - Hadke, Shreyash (2022)
Chalcogenide semiconductors offer excellent optoelectronic properties for their use in solar cells, exemplified by the commercialization of Cu(In,Ga)Se2- and CdTe-based photovoltaic technologies. Recently, several other chalcogenides have emerged as promising photoabsorbers for energy harvesting through the conversion of solar energy to electricity and fuels. The goal of this review is to summarize the development of emerging binary (Sb2X3, GeX, SnX), ternary (Cu2SnX3, Cu2GeX3, CuSbX2, AgBiX2), and quaternary (Cu2ZnSnX4, Ag2ZnSnX4, Cu2CdSnX4, Cu2ZnGeX4, Cu2BaSnX4) chalcogenides (X denotes S/Se), focusing especially on the comparative analysis of their optoelectronic performance metrics, electronic band structure, and point defect characteristics. The performance limiting factors of these photoabsorbers are discussed, together with suggestions for further improvement. Several relatively unexplored classes of chalcogenide compounds (such as chalcogenide perovskites, bichalcogenides, etc.) are highlighted, based on promising early reports on their optoelectronic properties. Finally, pathways for practical applications of emerging chalcogenides in solar energy harvesting are discussed against the backdrop of a market dominated by Si-based solar cells.